A Comparative Review of Financial Services Sector Commitments in the Selected Saarc Member Countries: Relevant Experiences for Nepal’s Accession to WTO - Research Department, Nepal Rastra Bank, International Finance Division (NRB Economic Review, 2002)
The world economy is integrating at an ever faster pace which can be reflected in both growing global trade and the increasing number of the World Trade Organization (WTO) members. To capture the benefits and advantages of global trade, Nepal has commenced the accession process for membership into WTO and is presently negotiating commitments in the various sectors of goods and services. As one of those sectors, the financial services sector (FSS), has major influence on domestic monetary and financial stability, the present paper examines the appropriate levels of commitments in FSS for Nepal through a comparative review of the FSS commitments by selected SAARC member countries; namely India, Pakistan and Sri Lanka. The analysis indicates that the majority of the financial services sector commitments occur through commercial presence although there exists large country- specific variations. The paper ends by recommending the appropriate level of financial services sector commitments for Nepal and suggesting on the essential preparation required in FSS with WTO membership.